Development of an in-house PCR for the detection of giardia lamblia in cat and dog stool samples - Hussein, Ikran Ahmed (2023)
Giardiasis is disease caused by a parasitic protozoan that can be transmitted through faecal-oral routes and carries a zoonotic transmission risk. Household pets, such as cats and dogs, can serve as carriers of this parasite, posing a transmission risk to vulnerable groups like children and the elderly. Although chronic and intermittent Giardia infections rarely lead to fatal outcomes, they can result in malnutrition or stunted growth in children and the elderly. Scheduling regular screenings of cat and dog stools is crucial to minimize the zoonotic risk of giardiasis. Stool microscopy is a robust and cost-effective method for detecting the parasite; however, its low sensitivity can lead to false negatives. On the other hand, PCR has higher sensitivity and can reduce false negatives due to the intermittent release of the parasite in stool. Thus, our study aimed to develop an in-house PCR method for detecting Giardia DNA in dog and cat stool samples. We established an axenic Giardia trophozoite culture and extracted Giardia DNA from these cells for use as an assay template. An in-house PCR was developed using Gia2029 and Gia2150c primers targeting a 250 bp amplicon. Additionally, we set up an internal control PCR (IC-PCR) using T7-promoter and T7-terminator primers targeting the Entamoeba histolytica SREHP gene (800 bp) in the pET14b-SREHP plasmid. The optimized annealing temperature for both Giardia-PCR and IC-PCR was 58 °C. The analytical limit of detection was approximately 20 pg of genomic DNA, equivalent to around 1000 trophozoites. In our preliminary PCR screening of Giardia in environmental stool samples from cats (n = 7) and dogs (n = 3) that tested negative by microscopy, we found unspecific amplicons in cat stool samples (6/7), but none in dog samples (0/3). All stool specimens showed positive PCR amplicons for the internal control gene, ruling out interference by PCR inhibitors. In conclusion, the PCR method based on Gia2029 and Gia2150c primers appears suitable for dog samples, while further evaluation via sequencing is required for cat samples.